2000
DOI: 10.1161/01.hyp.35.1.303
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Inhibits Migration of Vascular Smooth Muscle Cells With Inducible Nitric Oxide Synthase

Abstract: Abstract-Vascular smooth muscle cell (VSMC) migration participates in atherosclerosis and arterial restenosis after balloon angioplasty. Because these processes are enhanced in insulin-resistant states, our goal was to determine whether insulin affects VSMC migration and, if so, how. The migration of primary cultured VSMCs from canine femoral artery was measured with the use of a wound migration assay and related to cGMP levels. Insulin (1 nmol/L) did not affect migration or cGMP production in control cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Endothelia and adventitia were stripped away; the media of the arteries were minced, incubated at 37°C in a solution containing elastase (type V, Sigma) and collagenase (type I, Worthington Biochemical); and cultured VSMCs were prepared as previously described. 6 Cultured cells of passages 3 to 10 were used in experiments. Because a permissive amount of NO is necessary for insulin to stimulate cGMP production in cultured dog and rat VSMCs (Kahn et al 14 and data not shown), most experiments were performed with cells that had been induced to express iNOS as previously described.…”
Section: Cell Culturementioning
confidence: 99%
See 4 more Smart Citations
“…Endothelia and adventitia were stripped away; the media of the arteries were minced, incubated at 37°C in a solution containing elastase (type V, Sigma) and collagenase (type I, Worthington Biochemical); and cultured VSMCs were prepared as previously described. 6 Cultured cells of passages 3 to 10 were used in experiments. Because a permissive amount of NO is necessary for insulin to stimulate cGMP production in cultured dog and rat VSMCs (Kahn et al 14 and data not shown), most experiments were performed with cells that had been induced to express iNOS as previously described.…”
Section: Cell Culturementioning
confidence: 99%
“…Because a permissive amount of NO is necessary for insulin to stimulate cGMP production in cultured dog and rat VSMCs (Kahn et al 14 and data not shown), most experiments were performed with cells that had been induced to express iNOS as previously described. 6 …”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations